2022
DOI: 10.3390/plants11111408
|View full text |Cite
|
Sign up to set email alerts
|

Root Breeding in the Post-Genomics Era: From Concept to Practice in Apple

Abstract: The development of rootstocks with a high-quality dwarf-type root system is a popular research topic in the apple industry. However, the precise breeding of rootstocks is still challenging, mainly because the root system is buried deep underground, roots have a complex life cycle, and research on root architecture has progressed slowly. This paper describes ideas for the precise breeding and domestication of wild apple resources and the application of key genes. The primary goal of this research is to combine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 162 publications
0
3
0
3
Order By: Relevance
“…In this study, the root traits related to shape, colour, size and texture of RS, RGD, FC and CS were examined, and several putative genes were identified. It has been shown that plant root morphological changes are affected by nutrient elements [ 33 ], such as nitrogen (N). For RGD, we found a gene ( BVRB_5g097760 ) encoding protein NRT1/PTR FAMILY 6.3 related to the SNW_017567419.1_180782 marker.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the root traits related to shape, colour, size and texture of RS, RGD, FC and CS were examined, and several putative genes were identified. It has been shown that plant root morphological changes are affected by nutrient elements [ 33 ], such as nitrogen (N). For RGD, we found a gene ( BVRB_5g097760 ) encoding protein NRT1/PTR FAMILY 6.3 related to the SNW_017567419.1_180782 marker.…”
Section: Discussionmentioning
confidence: 99%
“…Важно отметить, что в условиях климатических изменений совершенствование сортов по величине и качеству урожая, стабильности и адаптивности, устойчивости к абиотическим и биотическим стрессам стано-вится еще более актуальным и требует углубленного и комплексного изучения физиологических, генетических, цитоэбриологических особенностей культур (6,12,60,68). Селекционеры во всем мире продолжают разрабатывать новые сорта с улучшенными характеристиками.…”
Section: иммунные к парше сорта яблони полученные с использованием до...unclassified
“…С е л е к ц и я к о л о н н о в и д н ы х с о р т о в я б л о н и. Компактность дерева -одно из требований современного интенсивного плодоводства (10,(58)(59)(60)(61). Этим свойством обладают колонновидные сорта яблони.…”
Section: иммунные к парше сорта яблони полученные с использованием до...unclassified
“…Важно отметить, что в условиях климатических изменений совершенствование сортов по величине и качеству урожая, стабильности и адаптивности, устойчивости к абиотическим и биотическим стрессам стано-вится еще более актуальным и требует углубленного и комплексного изучения физиологических, генетических, цитоэбриологических особенностей культур (6,12,60,68). Селекционеры во всем мире продолжают разрабатывать новые сорта с улучшенными характеристиками.…”
Section: иммунные к парше сорта яблони полученные с использованием до...unclassified